Analisis Kinerja Reksa Dana Nusantara PT Bhakti Asset Management dan Penyusunan Portfolio Optimum Teoritis Periode Januari – April 2005 - S., Tomy Gurtama; Mesha, Mesha (Journal the Winners: Economics, Business, Management, and Information System Journal, 2007)
The research objective is to find theoritical optimum portfolio of the Reksa Dana Nusantara (RDN) of BAM, using data from January – April 2005 (60 workdays).  The coefficient of variance (CV) will be  used to determine the stock rank, then it will be optimize with 3 methods ; linear programing, trial-error, and tableau method. The research found that RDN has Sharpe Performance Index (SPI) of 1.15 but the market can reach 1.60. The linear programing can not find optimum solution of portfolios consist of 9-5 stocks, but it can find the best portfolio consist in 3 stocks (TLKM, TKIM an CMNP) with SPI of 2.19. Overall, the research summarizes that RDN is still below the market performance.